Focus on fluid reasoning: The relationship between fluid reasoning and the Pattern of Strengths and Weaknesses model. Issue 3 (3rd July 2017) - Grant, Lisa M.; Prince, Pauline
ABSTRACT: The purpose of this paper is to examine the Fluid Reasoning Index of the Wechsler Intelligence Test for Children, Fifth Edition (WISC-V), and determine how fluid-reasoning skills relate to academic skill acquisition in the classroom setting. We also examine the myriad of ways within which learning and learning disabilities can be defined. Also, we plan to examine a brief review of the definition of a Specific Learning Disability and review some of the leading theories related to the Pattern of Strengths and Weaknesses model.